2011
DOI: 10.1002/jso.22136
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of paclitaxel/cisplatin as an adjuvant chemotherapy for patients with cervical cancer who underwent radical hysterectomy and systematic lymphadenectomy

Abstract: Postoperative chemotherapy using TP might be more beneficial for survival than adjuvant RT and can reduce postoperative complications for cervical cancer patients treated with radical hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 17 publications
2
62
1
Order By: Relevance
“…Therefore, systemic treatment is better for AC histology, and our results suggest that adjuvant CT might be more effective than RT/ CCRT for patients with AC. Several other studies have also shown that adjuvant CT might have some advantages over RT/CCRT regarding treatment-related complications (19,20).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, systemic treatment is better for AC histology, and our results suggest that adjuvant CT might be more effective than RT/ CCRT for patients with AC. Several other studies have also shown that adjuvant CT might have some advantages over RT/CCRT regarding treatment-related complications (19,20).…”
Section: Discussionmentioning
confidence: 96%
“…In the Cochrane Review, Rosa et al recently reported that the addition of platinum-based chemotherapy to adjuvant radiotherapy may improve survival in women with early-stage cervical cancer and reduce the risk factors for recurrence (20). Another study by Hosaka et al revealed that postoperative chemotherapy using paclitaxel/cisplatin may be more beneficial for survival than adjuvant radiotherapy and could reduce postoperative complications for cervical cancer patients who are treated with radical hysterectomy (21).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with paraaortic lymph node metastasis, 45 Gy of paraaortic radiotherapy was added. In cases with surgical margins that were close to the vagina, 21 Gy of high-dose vaginal brachytherapy was applied in 3 fractions. Vaginal brachytherapy was applied 0.5 cm below the vaginal mucosa, and the upper 4 cm of the vagina was treated.…”
mentioning
confidence: 99%
“…The 3-year overall survival was 93.8 % with TP versus 69.4 % with RT ( p = 0.02). The authors concluded that postoperative chemotherapy using TP may have a survival benefi t compared to adjuvant RT for patients with early-stage disease, along with reduced postoperative complications [ 7 ]. Japanese investigators reported similar results using adjuvant chemotherapy after radical hysterectomy for intermediate-and high-risk stage IB-IIA cervical cancer [ 8 ].…”
Section: What Is the Evidence For Adjuvant Chemotherapy After Surgery?mentioning
confidence: 95%